Universum based Lagrangian twin bounded support vector machine to classify EEG signals. (September 2021) - Kumar, Bikram; Gupta, Deepak
Highlights: An efficient variant of support vector machine called universum based Lagrangian TBSVM is proposed. Classification of electroencephalogram signals is done using universum data which is used to give the prior knowledge about the distribution of data. Several feature extraction techniques have been implemented to get the most significant features for EEG signals. Statistical analysis is performed to show the effectiveness and acceptability of the proposed ULTBSVM on real-world datasets. Abstract: Background and objective: The detection of brain-related problems and neurological disorders like epilepsy, sleep disorder, and so on is done by using electroencephalogram (EEG) signals which contain noisy signals and outliers. Universum data contains a set of a sample that does not belong to any of the concerned classes and serves as the advanced knowledge about the data distribution. Earlier information has been utilized viably in improving classification performance. Recently a novel universum support vector machine (USVM) was proposed for EEG signal classification and further, a universum twin support vector machine (UTWSVM) was proposed based on USVM to improve the performance. Inspired by USVM and UTWSVM, this paper suggests a novel method called universum based Lagrangian twin bounded support vector machine (ULTBSVM), where universum data is utilized to incorporate the prior information about the data distribution to classify healthy and seizure EEG signals. Methods: In the proposed ULTBSVM the square of the 2-norm of the slack variables is used to formulate the objective function strongly convex; hence it always gives unique solutions. Unlike twin support vector machine (TWSVM) and universum twin support vector machine (UTWSVM), the proposed ULTBSVM is having regularization terms that follow the structural risk minimization (SRM) principle and enhance the stability in the dual formulations, make the model well-posed and prevents the overfitting problem. Here, interracial EEG data have been considered as universum data to classify healthy and seizure signals. Several feature extraction techniques have been implemented to get important noiseless features. Results: Several EEG datasets, as well as publicly available UCI datasets, are utilized to assess the performance of the proposed method. An analytical comparison has been performed of the proposed method with USVM and UTWSVM to detect seizure and healthy signals and for real-world data, the ULTBSVM is compared with the universum based models as well as TWSVM and the proposed method gives better results in most of the cases as compared to the other methods. Conclusion: The results clearly show that ULTBSVM is a potential method for the classification of EEG signals as well as real-world datasets having interracial data as universum data. Here we have used universum points for the binary class classification problem, but one can extend and use it for multi-class classification problems as well.